PS 18-18 Economic evaluation of a school-based education programme to reduce salt intake in children and their families in China. (September 2016) - LI, Xian; Jan, Stephen; Yan, Lijing L.; Hayes, Alison; Wang, Haijun; Feng, Xiangxian; Niu, Wenyi; He, Feng J.; Ma, Jun; Han, Yanbo; MacGregor, Graham A.; Wu, Yangfeng
Abstract : Objective: The School-based Education Programme to Reduce Salt Intake in Children and Their Families study was a cluster randomised control trial among 28 primary schools in Changzhi, China. It achieved a significant effect in lowering systolic blood pressure (SBP) in all adults by 2.3 mmHg and in elderly (defined as family members with age> = 60 years) by 9.5 mmHg. The aim of this study was to assess the cost-effectiveness of this salt reduction programme. Design and Method: Costs of the intervention were assessed using an ingredients approach to identify resource use. A trial-based incremental cost-effectiveness ratio (ICER) was estimated based on the observed effectiveness in lowering SBP. A Markov model based on the observed effect from elderly only was used to enable extrapolation of the long-term cost-effectiveness of the program scaled up nationwide. Findings were presented in terms of an incremental cost per quality-adjusted life year (QALY). Results: The intervention costed US$16.96 per family and yielded an ICER of US$2.69 per mmHg reduction of SBP compared with control group. If scaled up nationwide for 10 years, it would reach 93.75 million families and would avert 22, 914 acute myocardial infarction deaths and 61, 506 stroke deaths in China. This would represent a gain of 380, 694 QALYs and a saving of US$1.0 billion in direct medical cost over a 10-year time frame, translating into US$1, 711 per QALY gained. This estimation is much lower than the cost-effective threshold of cost per QALY of $50, 000, and lower than the WHO-CHOICE highly cost-effective threshold of once the country's annual gross domestic product per capita ($7, 595 for China in 2014). Conclusions: Our analysis demonstrated that the proposed salt reduction strategy is highly cost-effective, and if scaled up nationwide, the benefits would be substantial.